Analysis of cash flow from operating activities, cash flow from investing activities, cash flow from financing activities, gross profit margin, and earnings per share on the stock price - Hakim, Shintia; Pasaribu, Elsa Dwi Suryani; Gulo, Dobinikus; Katharina, Ninta; Kalsum, Umi (Priviet Social Sciences Journal, 2023)
Our research aims to analyze whether operating cash flow, investment cash flow, financing cash flow, Gross Profit Margin, and Earnings Per Share have an impact on stock prices. Our research falls under quantitative research. The sampling was conducted using purposive sampling, resulting in 19 companies that fit the category. The hypothesis was tested using multiple linear regression. The research findings present various results. Therefore, the conclusion from the research is that operating cash flow and investment cash flow have a significant and insignificant impact on the stock prices of food and beverage companies, while financing cash flow, Gross Profit Margin, and Earnings Per Share do not have a significant impact on the stock prices of food and beverage companies.